Intrinsic versus extrinsic variability of analogue sand-box experiments – Insights from statistical analysis of repeated accretionary sand wedge experiments. (June 2015) - Santimano, Tasca; Rosenau, Matthias; Oncken, Onno
Abstract: Analogue models are not perfectly reproducible even under controlled boundary conditions which make their interpretation and application not always straight forward. As any scientific experiment they include some random component which can be influenced both by intrinsic (inherent processes) and extrinsic (boundary conditions, material properties) sources. In order to help in the assessment of analogue model results, we discriminate and quantify the intrinsic versus extrinsic variability of results from "sandbox" models of accretionary wedges that were repeated in a controlled environment. The extrinsic source of variability, i.e. the parameter varied is the nature of the décollement (material, friction and thickness). Experiment observables include geometric properties of the faults (lifetime, spacing, dip) as well as wedge geometry (height, slope, length). For each variable we calculated the coefficient of variance (CV) and quantified the variability as a symmetric distribution (Normal, Laplacian) or asymmetric distribution (Gamma) using a Chi squared test (χ 2 ). Observables like fault dip/back thrust dip (CV = 0.6–0.7/0.2–0.6) are less variable and decrease in magnitude with decreasing basal friction. Variables that are time dependent like fault lifetime (CV = 0.19–0.56) and fault spacing (CV = 0.12 – 0.36) have a higher CV consequently affecting the variability of wedge slope (CV = 0.12–0.33). These observables also increase in magnitude with increasing basal friction. As the mechanical complexity of the evolving wedge increases over time so does the CV and asymmetry of the distribution. In addition, we confirm the repeatability of experiments using an ANOVA test. Through the statistical analysis of results from repeated experiments we present a tool to quantify variability and an alternative method to gaining better insights into the dynamic mechanics of deformation in analogue sand wedges. Highlights: We statistically quantify variability in repeated analogue experiments. Extrinsic source of variability is due to varying basal friction. A probability based comparison between the different observables is presented. The ANOVA test is used to confirm the repeatability of results. We show that the mechanics of deformation control the variability.